Small Molecules Targeting Ataxia Telangiectasia and Rad3-Related (ATR) Kinase: An Emerging way to Enhance Existing Cancer Therapy - Andrs, Martin; Korabecny, Jan; Nepovimova, Eugenie; Jun, Daniel; Hodny, Zdenek; Kuca, Kamil (Current Cancer Drug Targets, 2016)
The main aim of current cancer research is to find a way to selectively affect the tumor cells, while leaving normal cells intact. Ataxia telangiectasia and Rad3-related kinase (ATR), a member of the phosphatidylinositol-3-related protein kinases (PIKK), represents a candidate target for achieving this goal. ATR kinase is one of the main kinases of the DNA damage response signaling pathway and responds to DNA damage caused by replication stress and various genotoxic agents (i.e. chemotherapy, ionizing radiation, ultraviolet light). ATR activation triggers cell cycle checkpoints, DNA repair and apoptosis, but also resistance of tumor cells to DNA damaging agents, through stress support under replication stress. Thus, the inhibition of ATR leads to increased effectiveness of cancer therapy and in addition enables highly selective targeting of cancer cells through synthetic lethal interactions. Despite this great potential, only a few potent and selective inhibitors of ATR kinase have been developed to date. However, those which have been developed provide great promise, and are under evaluation in many current preclinical and clinical trials. The purpose of this review is to summarize the potential of ATR inhibitors and the medicinal chemistry efforts which resulted in their identification.
Keywords: cancer